2014
DOI: 10.1039/c3cc48667b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled monolayers of gold nanostars: a convenient tool for near-IR photothermal biofilm eradication

Abstract: Monolayers of gold nanostars (GNS) are grafted on mercaptopropyltrimethoxysilane-coated glass slides. In the formed monolayers the localized surface plasmon resonance of GNS can be tuned in the 700-1100 nm range. Upon laser excitation of the nearIR LSPR an efficient photothermal response is observed, inducing local hyperthermia and efficient killing of Staphylococcus aureus biofilms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(121 citation statements)
references
References 20 publications
3
118
0
Order By: Relevance
“…For S-AuNS, this shift was 58 nm on average, which is close to the blue shift of about 50 nm reported in other studies when monolayers of AuNS were grafted on glass slides. 52,57 This shift could be due to the change in the AuNS local refractive index (n), following the change of medium from water (n = 1.333) to air (n = 1.0003). 58 In fact, previous investigation of this effect by grafting AuNS on the internal wall of a glass cuvette and recording the extinction spectra using solvents of different n,…”
Section: Synthesis Of Self-assembled Monolayers Of Auns Grafted On Glmentioning
confidence: 99%
See 1 more Smart Citation
“…For S-AuNS, this shift was 58 nm on average, which is close to the blue shift of about 50 nm reported in other studies when monolayers of AuNS were grafted on glass slides. 52,57 This shift could be due to the change in the AuNS local refractive index (n), following the change of medium from water (n = 1.333) to air (n = 1.0003). 58 In fact, previous investigation of this effect by grafting AuNS on the internal wall of a glass cuvette and recording the extinction spectra using solvents of different n,…”
Section: Synthesis Of Self-assembled Monolayers Of Auns Grafted On Glmentioning
confidence: 99%
“…To fabricate MEF substrates based on AuNS, a self-assembly method was employed (Figure 1b, i-ii), 52 inspired by previous reports on the silanization of glass surfaces, 44 and their use to obtain monolayers of silver nanoparticles with antibacterial properties, 53 or AuNS for photothermal bacterial eradication. 52 The…”
Section: Synthesis Of Self-assembled Monolayers Of Auns Grafted On Glmentioning
confidence: 99%
“…Furthermore, it has been observed that the coating of glass materials with gold nanoparticles proved to be very efficient in photothermal biofilm laser treatment against S. aureus biofilms, suggesting the possibility of fabricating medical devices with the same coating: once internalized, they would not need to be removed if a biofilm is formed on their surface but may be treated in situ, i.e., through tissues, avoiding surgical removal ( Figure 5) [79].…”
Section: Photomedicine -Advances In Clinical Practicementioning
confidence: 99%
“…In a recent study, 34 monolayers of gold nanostars were synthesized by lauryl sulfobetaine-driven seeded growth method. The anti-biofilm activity was evaluated by preparing 32 round glass slides (1.0 cm in diameter) using localized surface plasmon resonance spectroscopy (802 nm, s =12) and setting the surface concentration of the adsorbate on the gold surface to 3.0 mg/cm² (s =0.4).…”
Section: Gold Nanostarsmentioning
confidence: 99%
“…After exposure to 808 nm laser, the monolayers of gold nanostars generated a rise in tumor temperature (hyperthermia), which resulted in the efficient killing of the S. aureus biofilm. 34 A class of shape-and size-selective antimicrobial agents was developed in a study conducted by Borovička et al 35 The experiment consisted of the fabrication of imprinted colloid particles using cell templates by the fragmentation of silica shells. The increased contact area between the target cell and the colloidal imprint led to the mechanism of recognition, which can help develop "colloid antibodies" for efficient shape-selective binding (Figure 3).…”
mentioning
confidence: 99%